Live Facial Recognition Treats Everyone as a Potential Suspect, Undermining Privacy and Eroding Presumed Innocence - CIVICUS (Inter Press Service, 2025)
The rapid expansion of live facial recognition technology across the UK raises urgent questions about civil liberties and democratic freedoms.